Detection of Extended‐Spectrum β‐Lactamase and Plasmid‐Mediated Quinolone Resistance Determinants in Escherichia coli Isolates from Retail Meat in China. Issue 5 (11th April 2015) - Yu, Tao; Jiang, Xiaobing; Fu, Kaifei; Liu, Biyun; Xu, Dong; Ji, Shengdong; Zhou, Lijun
Abstract The aim of this study was to investigate the presence of extended‐spectrum β‐lactamase (ESBL) and plasmid‐mediated quinolone resistance (PMQR) genes in Escherichia coli isolated from retail meat samples in Henan Province, China. E. coli isolates were detected in 179 of 645 (27.7%) retail meat samples. Resistance of these isolates to antimicrobials was commonly observed, with 78.2% of isolates resistant to streptomycin, 74.3% resistant to tetracycline and 54.2% resistant to trimethoprim/sulfamethoxazole. Of the 179 isolates, 30 (16.7%) expressed ESBL, with blaTEM‐1 (n = 17) and blaCTX‐M‐14 (n = 9) most commonly mediating the ESBL phenotype. PMQR genes were present in 14 isolates (7.8%), with qnr and aac(6′)‐Ib‐cr detected alone or in combination in nine (5.0%) and seven isolates (3.9%), respectively. The qnr genes detected included qnrS1 (n = 5), qnrA1 (n = 3), and qnrB4 (n = 1). The qepA gene was absent among these isolates. CTX‐M‐14 was the most prevalent ESBL type among the PMQR‐positive isolates. The qnr and aac(6′)‐Ib‐cr genes were found to co‐reside and be co‐transferred with blaCTX‐M‐14 or blaTEM‐1 in five isolates. Our data suggest that retail meat may act as a reservoir for multi‐resistant E. coli and may facilitate the dissemination of resistance genes.